Os rios e pântanos nas primeiras representações cartográficas da vila Campos dos Goitacazes: imaginação geográfica e disputas de poder (final do século XVIII até começos do XIX) - Maria Isabel de Jesus Chrysostomo (Confins)
This paper analyzes the role of cartographic productions in the invention of a territory, formed at the point of articulation between nature and culture. We will find this aspect from the reading of two maps and two plants produced between the 18th and 19th centuries in the Campos dos Goitacazes-RJ. As a result of the movement of interiorization of the colony, these representations indicate different stages of the process of conquest and appropriation of the plain once inhabited by the silvícolas of the Goitacá nation. In associating the territorial project that gave birth to these maps, we tried to discuss how these "technical instruments" served to dilate the power of the Crown and to dominate the two natures: those considered wild and the marshes and ponds that characterize the region.